VARIABILITY IN WATER USE, CROP WATER PRODUCTIVITY AND PROFITABILITY OF RICE AND WHEAT IN RECHNA DOAB, PUNJAB, PAKISTAN - M. Usman; I. Kazmi; T. Khaliq; A. Ahmad; M. F. Saleem; A. Shabbir (Journal of Animal and Plant Sciences, 2012)
Variation in water use, crop water productivity and profitability was studied across the sampled watercourses of the Lagar Distributary of Upper Gogera branch of Lower Chenab Canal. Stratified random sampling technique was used to identify and interview 120 farmers in total, ten each at head, middle and tail reaches of the four sampled watercourse using well-structured questionnaire. Surface as well as groundwater is being used in the study area, either separately or jointly, with groundwater as a major shareholder. The area underground water irrigation increased from 58 acres at head to 113.8 acres at tail. Groundwater productivity of wheat was found higher at head (0.97 kg m-3) than middle (0.96 kg m-3) and tail (0.89 kg m-3). On the other hand, groundwater productivity of rice did not vary across the water channel. The main reason was that water demand of the crop was mainly met by groundwater at all locations. The % share of different inputs cost in total cost of production was determined. Fertilizer was found as the major contributor among land preparation, labor cost, chemicals, irrigation, seed and harvesting etc. Favourable soil conditions and more reliance on groundwater supplies resulted in greater gross value of product (GVP) and gross margins (GM) at the tail. At tail ends it is needed either to increase canal water allowance or government support to install electricity tubewells on sharing/collective basis. There is a need to promote resource conservation techniques like zero tillage, laser land leveling and watercourse lining to increase crop water productivity. This will also help to conserve groundwater.
Keywords: Water use; Crop water productivity; Profitability.